Seroprevalence for severe fever with thrombocytopenia syndrome virus among the residents of Miyazaki, Japan: An epidemiological study - Hidaka, Kazuhiro; Mitoma, Shuya; Norimine, Junzo; Shimojima, Masayuki; Kuroda, Yoshiki; Hinoura, Takuji (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2024)
Severe fever with thrombocytopenia syndrome (SFTS) is a tick-borne infectious disease caused by the SFTS virus (SFTSV). The Miyazaki Prefecture has the highest number of SFTS cases in Japan and requires countermeasures for prevention. In this study, we aimed to conduct an epidemiological survey in Miyazaki Prefecture to determine the exposure conditions of SFTSV by measuring the seroprevalence among residents of Miyazaki and to evaluate the factors that influence the endemicity of SFTS. The survey was conducted between June 2014 and April 2019 in all 26 municipalities in Miyazaki Prefecture. SFTSV antibodies were detected using an enzyme-linked immunosorbent assay in the blood samples of 6013 residents (3184 men and 2829 women). A questionnaire-based survey of the living environment was also conducted. Multiple logistic regression analysis revealed that age and occupation were significant factors related to the proportion of participants with an optical density (OD) value > 0.2 and a seroprevalence of 0.9 % (54/6013). Seven seropositive individuals (0.1 %) with an OD value of >0.4 were identified (three men and four women, aged 54–69 years), and all were asymptomatic. One participant had a higher OD than the positive control. Although SFTS is endemic in Miyazaki Prefecture, Japan, its seroprevalence is relatively low. Since some risk areas in Miyazaki prefecture have been identified, it is important to enhance awareness of SFTS in residences and reduce contact with ticks, especially in high-risk areas.